KOMUNIKASI DAN KOORDINASI PENYELENGGARAAN PELAYANAN UMUM BIDANG ANGKUTAN DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU - Lilla Mardhatillah; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research to describe the communication and coordination of the department oftransportation made in improving service in the field of urban transportation. The focus ofthis issue see how the mechanisms that have been carried out the transportation departmentand the traffic unit in communication and coordination. Are there any barriers incommunication and coordination that has been done, can be searched appropriaterecommendations to address these issues. In Pekanbaru mayor regulation number 17 of 2008about the details of functions and working procedures of the Department of Communicationand Information neighbor explained that where the public service, especially for the field ofpublic transport. One of the points of Mayor Regulation Number 17 of 2008 which lead andcoordinate all activities of the officers and staff offices. That in conducting the affairs ofgovernment in serving the public need for communication and coordination between theDepartment of Transportation is Information Communication and Traffic unit pekanbarucity.This research using Fayol, Koontz and O'Donnell theory, where in it there are fourindicators: 1. Communication. 2. Cooperation. 3. Division of tasks. 4. Conference andmeeting. The type of research is qualitative research with descriptive methods, its purpose isto analyze and describe the communication and coordination of transport sector provision ofpublic services.The results of research in the field stating that the communication and coordinationhas been carried out the transportation department and the traffic unit has not been optimal.In coordinating the transportation department should pay more attention to implementationof the objectives, so that meeting participants receive appropriate guidance to the creation oftwo-way communication. Coordination is still constrained by problems such ascommunications made ineffective, coordination has not been implemented, so that betweenthose who give and receive the policy are not well coordinated.Key words: Communication, Coordination, Public Service